2010
DOI: 10.1016/j.solidstatesciences.2010.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of [4-(2,4-dichlorophenoxybutyrate)-zinc layered hydroxide] nanohybrid

Abstract: A new layered organic-inorganic nanohybrid material in which an agrochemical, 4-(2,4dichlorophenoxy)butyrate (DPBA) is intercalated into inorganic interlayers of zinclayeredhydroxide (ZLH) was synthesized by direct reaction of aqueous DPBA solution with zinc oxide. The resulting nanohybrid is composed of the organic moieties, DPBA sandwiched between ZLH inorganic interlayers. The nanohybrid afforded well ordered crystalline layered structure, a basal spacing of 29.6 Å, 23.5% carbon (w/w) and 47.9% (w/w) loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…It is clear that an ideal level of pH in the blood is about 7.4, and even changing this level slightly may have fatal consequences. Therefore, release of gallic acid from nanoparticles was determined using a 0.0001 M aqueous solution of Na 2 CO 3 32 and Na 3 PO 4 buffered solutions of pH 4.8 [33][34][35][36][37][38][39] and 7.4 37,38,40,41 at 37°C. The gallic acid released was measured at preset times using ultraviolet-visible spectrophotometry at 264 nm.…”
Section: Characterizationmentioning
confidence: 99%
“…It is clear that an ideal level of pH in the blood is about 7.4, and even changing this level slightly may have fatal consequences. Therefore, release of gallic acid from nanoparticles was determined using a 0.0001 M aqueous solution of Na 2 CO 3 32 and Na 3 PO 4 buffered solutions of pH 4.8 [33][34][35][36][37][38][39] and 7.4 37,38,40,41 at 37°C. The gallic acid released was measured at preset times using ultraviolet-visible spectrophotometry at 264 nm.…”
Section: Characterizationmentioning
confidence: 99%
“…The release of cetirizine from CETN into the medium of phosphate buffer solution at pH 7.4 and pH 4.8 [22][23][24] was achieved by adding about 85 mg of CETN into 250 mL buffer solutions. The accumulated amount of cetirizine released into the solutions was measured at different times using a UV-visible spectrophotometer at 231 nm.…”
Section: Loading and Release Amounts Of Cetirizine In Cetnmentioning
confidence: 99%
“…Release profiles for cetirizine from CETN ( Figure 7I) show results similar to those of other drugs, such as 5-flurouracil, camptothecin, naproxen, l-Dopa, and 5-florocytosine, found in the literature. 22,24,[35][36][37][38] Release kinetics of cetirizine from CETN In order to better understand the mechanism of the release of cetirizine from CETN, the results of the kinetic studies were analyzed using pseudo-first order (Equation 1), 39 pseudo-second order (Equation 2), 40 ln (q e −q t ) = ln q e − k 1 t…”
Section: Release Behavior Of Cetirizinementioning
confidence: 99%
“…However, to the best of our knowledge, little work has been published on the use of ZnO as a starting material to intercalate drug actives. 35,36 Therefore, the main objective of this work was to explore the potential use of ZnO as a starting material for the intercalation of EA for the formation of a new EA-ZLH nanohybrid (EAN). The resulting nanohybrid was then used as a controlled release formulation of drug active EA.…”
Section: Introductionmentioning
confidence: 99%
“…Total disappearance of the intense peaks of ZnO phase indicated that the sample EAN is pure phase and the ZnO was completely converted to ZLH. 36 The formation of EAN is believed to occur through a dissociation-deposition mechanism 36,49 which takes place in the nonaqueous solution of hydrated EA. The mechanism is composed of three steps: …”
mentioning
confidence: 99%